2021
DOI: 10.1128/spectrum.01585-21
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of the Direct Contribution of Candida auris ERG11 Mutations to Clinical Triazole Resistance

Abstract: Candida auris is an emerging multidrug-resistant and health care-associated pathogen of urgent clinical concern. The triazoles are the most widely prescribed antifungal agents worldwide and are commonly utilized for the treatment of invasive Candida infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 20 publications
(38 reference statements)
3
39
0
2
Order By: Relevance
“…In C. auris isolates, fluconazole resistance has been correlated with three amino acid substitutions in ERG11 : V125A/F126L, Y132F, and K143R ( 4 ). These mutations have been shown to increase fluconazole MICs by ~16-fold ( 10 ); however, mutations in ERG11 alone cannot explain the very high levels of resistance (MICs >256μg/mL fluconazole) observed in many C. auris isolates. Activating mutations in the transcriptional regulator of drug efflux pumps, TAC1B , have also been shown to be important for high levels of fluconazole resistance ( 11 ), and deletion of TAC1B abrogates resistance ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…In C. auris isolates, fluconazole resistance has been correlated with three amino acid substitutions in ERG11 : V125A/F126L, Y132F, and K143R ( 4 ). These mutations have been shown to increase fluconazole MICs by ~16-fold ( 10 ); however, mutations in ERG11 alone cannot explain the very high levels of resistance (MICs >256μg/mL fluconazole) observed in many C. auris isolates. Activating mutations in the transcriptional regulator of drug efflux pumps, TAC1B , have also been shown to be important for high levels of fluconazole resistance ( 11 ), and deletion of TAC1B abrogates resistance ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the binding affinity of fluconazole to its target is reduced. The isolate with these mutations exhibited a 16-fold increase in fluconazole minimum inhibitory concentration (MIC) [ 8 ]. Missense mutations and silent point mutations in ERG3 are thought to be responsible for the mis-synthesized sterols and high levels of drug resistance [ 9 ].…”
Section: Antifungal Resistances Mediated By Genetic Mutationsmentioning
confidence: 99%
“…The resistance to azoles in C. auris is multifactorial; it has been shown that certain mutations in ERG11 (15,(23)(24)(25)(26)(27)(28)(29)(30)(31) and overproduction of Cdr1p (32)(33)(34)(35)(36) contribute to resistance to fluconazole (FLZ). In multiple Candida species, the transcriptional regulator Mrr1 also plays a role in FLZ resistance (37)(38)(39)(40)(41)(42)(43)(44)(45), and Mayr and colleagues (46) found three C. auris homologs of the transcriptional regulator Mrr1, and showed that one of them, MRR1a, modestly affected fluconazole resistance.…”
Section: Introductionmentioning
confidence: 99%